FORMING THE RIGHT PRONUNCIATION IN LANGUAGE TEACHING FORMATION OF SKILLS - Ernazarova Khilola Ergashevna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article is devoted to the formation of correct pronunciation, skills and competencies in teaching a foreign language in accordance with the requirements of the CEFR, which examines the features of teaching the pronunciation of a foreign language at all stages of language learning and different views on this issue.